EUFOREA consensus on biologics for CRSwNP with or without asthma. Issue 12 (15th July 2019) - Fokkens, Wytske J.; Lund, Valerie; Bachert, Claus; Mullol, Joaquim; Bjermer, Leif; Bousquet, Jean; Canonica, Giorgio W.; Deneyer, Lauren; Desrosiers, Martin; Diamant, Zuzana; Han, Joseph; Heffler, Enrico; et al.
Abstract: Novel therapies such as type 2 targeting biologics are emerging treatment options for patients with chronic inflammatory respiratory diseases, fulfilling the needs of severely uncontrolled patients. The majority of patients with chronic rhinosinusitis with nasal polyps (CRSwNP) and over half of patients with asthma show a type 2 inflammatory signature in sinonasal mucosa and/or lungs. Importantly, both chronic respiratory diseases are frequent comorbidities, ensuring alleviation of both upper and lower airway pathology by systemic biological therapy. Type 2‐targeting biologics such as anti‐IgE, anti‐IL4Rα, anti‐IL5, and anti‐IL5Rα have entered the market for selected pheno/endotypes of asthma patients and may soon also become available for CRSwNP patients. Given the high prevalence of chronic respiratory diseases and the high cost associated with biologics, patient selection is crucial in order to implement such therapies into chronic respiratory disease care pathways. The European Forum for Research and Education in Allergy and Airway Diseases (EUFOREA) organized a multidisciplinary Expert Board Meeting to discuss the positioning of biologics into the care pathways for CRSwNP patients with and without comorbid asthma.